\[\boxed{\mathbf{793\ (793).\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[a_{1} = 7;\ \ d = 2;\ \ \ S_{n} > 315\]
\[S_{n} = \frac{2a_{1} + d(n - 1)}{2} \cdot n =\]
\[= \frac{2 \cdot 7 + 2 \cdot (n - 1)}{2} \cdot n =\]
\[= (7 + n - 1) \cdot n = 6n + n^{2}\]
\[6n + n^{2} > 315\]
\[n^{2} + 6n - 315 > 0\]
\[n_{1} + n_{2} = - 6,\ \ n_{1} = 15\]
\[n_{1}n_{2} = - 315,\ \ \]
\[n_{2} = - 21\ (не\ удовлетворяет).\]
\[Ответ:n = 16.\]
\[\boxed{\mathbf{793.\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[1)\ y = x² \Longrightarrow и\ возрастает,\ и\]
\[\ убывает;\]
\[2)\ y = \frac{2}{x}\ \]
\[пусть\ x_{1} = 1;\ \ x_{2} = 2 \Longrightarrow \ \ x_{1} <\]
\[< x_{2} \Longrightarrow \ f\left( x_{1} \right) = 2;\ \]
\[\text{\ f}\left( x_{2} \right) = 1 \Longrightarrow\]
\[\Longrightarrow f\left( x_{1} \right) > f\left( x_{2} \right) \Longrightarrow\]
\[\Longrightarrow убывающая;\]
\[3)\ y = - 2x \Longrightarrow убывающая \Longrightarrow \text{\ \ }\]
\[\Longrightarrow - 2 < 0;\]
\[4)\ y = 2x \Longrightarrow возрастающая \Longrightarrow\]
\[\Longrightarrow \text{\ \ }2 > 0.\]